AKT-mediated phosphorylation of ATG4B impairs mitochondrial activity and enhances the Warburg effect in hepatocellular carcinoma cells. Issue 4 (3rd April 2018) - Ni, Zhenhong; He, Jintao; Wu, Yaran; Hu, Changjiang; Dai, Xufang; Yan, Xiaojing; Li, Bo; Li, Xinzhe; Xiong, Haojun; Li, Yuming; Li, Song; Xu, Liang; et al.
ABSTRACT: Phosphorylation is a major type of post-translational modification, which can influence the cellular physiological function. ATG4B, a key macroautophagy/autophagy-related protein, has a potential effect on the survival of tumor cells. However, the role of ATG4B phosphorylation in cancers is still unknown. In this study, we identified a novel phosphorylation site at Ser34 of ATG4B induced by AKT in HCC cells. The phosphorylation of ATG4B at Ser34 had little effect on autophagic flux, but promoted the Warburg effect including the increase of L-lactate production and glucose consumption, and the decrease of oxygen consumption in HCC cells. The Ser34 phosphorylation of ATG4B also contributed to the impairment of mitochondrial activity including the inhibition of F1 Fo-ATP synthase activity and the elevation of mitochondrial ROS in HCC cells. Moreover, the phosphorylation of ATG4B at Ser34 enhanced its mitochondrial location and the subsequent colocalization with F1 Fo-ATP synthase in HCC cells. Furthermore, recombinant human ATG4B protein suppressed the activity of F1 Fo-ATP synthase in MgATP submitochondrial particles from patient-derived HCC tissues in vitro. In brief, our results demonstrate for the first time that the phosphorylation of ATG4B at Ser34 participates in the metabolic reprogramming of HCC cells via repressing mitochondrial function, which possibly results from the Ser34 phosphorylation-induced mitochondrial enrichment of ATG4B and the subsequent inhibition of F1 Fo-ATP synthase activity. Our findings reveal a noncanonical working pattern of ATG4B under pathological conditions, which may provide a scientific basis for developing novel strategies for HCC treatment by targeting ATG4B and its Ser34 phosphorylation.